Clinical Effectiveness of Influenza Vaccination After Allogeneic Hematopoietic Stem Cell Transplantation: A Cross-sectional, Prospective, Observational Study. (15th September 2018) - Piñana, José Luis; Pérez, Ariadna; Montoro, Juan; Giménez, Estela; Gómez, María Dolores; Lorenzo, Ignacio; Madrid, Silvia; González, Eva María; Vinuesa, Víctor; Hernández-Boluda, Juan Carlos; Salavert, Miguel; Sanz, Guillermo; et al.
Abstract: Background: Vaccination is the primary method for preventing influenza respiratory virus infection (RVI). Although the influenza vaccine is able to achieve serological responses in some allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients, its clinical benefits are still uncertain. Methods: In this prospective, cross-sectional study, we retrospectively analyzed the effect of inactivated trivalent influenza vaccination on the prevalence of influenza RVI in a consecutive cohort of 136 allo-HSCT adult recipients who developed 161 RVI over 5 flu seasons (from 2013 to 2018). Respiratory viruses in upper– and/or lower–respiratory tract specimens were tested using multiplex polymerase chain reaction panel assays. Results: Overall, we diagnosed 74 episodes (46%) of influenza RVI in 70 allo-HSCT recipients. Influenza RVI occurred in 51% of the non-vaccinated compared to 36% of the vaccinated recipients ( P = .036). A multivariate analysis showed that influenza vaccination was associated with a lower prevalence of influenza RVI (odds ratio [OR] 0.39, P = .01). A multivariate risk factor analysis of lower–respiratory tract disease (LRTD) identified 2 conditions associated with the probability of influenza RVI progression: influenza vaccination (OR 0.12, 95% confidence interval [CI] 0.014–1, P = .05) and a high-risk immunodeficiency score (OR 36, 95% CI 2.26–575, P = .011). Influenza vaccination was also associated with a lower likelihood of an influenza-related hospital admission (14% vs 2%, P = .04). Conclusions: This study shows that influenza vaccination may have a clinical benefit in allo-HSCT recipients with virologically-confirmed RVI, in terms of a lower influenza RVI prevalence, slower LRTD progression, and lower likelihood of hospital admission. Abstract : Influenza vaccination after allogeneic hematopoietic stem cell reciept was associated with a lower prevalence of influenza respiratory virus infection (RVI) among recipients with virologically-confirmed RVIs. Vaccination and a high-risk immunodeficiency score impacted influenza virus lower–respiratory tract disease progression.